O caso clínico de Isadora: a intervenção psicológica na primeira crise psicótica - Melo, Guiomar Marques Gouveia de (2001)
The objective of this research is to demonstrate that psychological intervention during the first psychotic crisis can sinificantly help the therapist in his clinical work. The Case Study, object of this research, entitled The Isadora Clinical Case , was inspired by our clinical psychotherapeutic work with a young patient. During this clinical psychoterapeutic process we discovered the importance of the psychological intervention, when the psychotic patient, in her first crisis, receives psychological help simultaneously with the psychiatric treatment. Utilizing the strategy of the psychological intervention right from the first psychotic crisis, it was possible to minimize its desasterous effects on the patient s personality. The implementation of this research was possible due to the patient narratives during psychotherapeutic sessions, as well from everything she wrote about her dreams and her delirius. We collected the data that seemed most important and, from this clinical material, we proceeded with a psychoanalytic reading, using as theoretical reference Freud s doutrine and the comments of some of Lacan s disciples. We hope that this research will show how the psychotic patient, after psychological intervention, becomes less resistent to the psychotherapeutic process, which will help to rebuild his inner world, in more favorable conditions, having improved his defense system, his capacity to relate to reality, and also, with the persons that form his surrouding world that he tries to live with